1979
DOI: 10.1142/s0192415x79000180
|View full text |Cite
|
Sign up to set email alerts
|

Plants with Hypotensive, Antiatheromatous and Coronarodilatating Action

Abstract: However great the success in the therapy of hypertension, atherosclerosis and ischemic heart disease has been gained today by recent efficient drugs, the definite healing of patients is not yet attained. The late discovery of reserpine, such an efficient drug of plant origin against hypertension, convinced so far reluctant scientists to consider the chemical compounds of the plant world. With respect to this traditional medical knowledge, it seems necessary to define more accurately the specificity of these he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
2

Year Published

1988
1988
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(39 citation statements)
references
References 0 publications
2
35
0
2
Order By: Relevance
“…In yet another study in Germany [56], on administration of garlic powder to 24 hypertensive patients for 3 months, their supine diastolic blood pressure fell by 11% and their standing systolic pressure fell by 12% as compared to non significant fall in a control of 23 patients. Similar results were obtained by Petkov in Russia also [57]. Onion and garlic organic sulfides can combine with NO and enhance vasodialation and reduce hypertension in mammals according to Ku et al [58] and Schwartz et al [37].…”
Section: Effect On Blood Pressuresupporting
confidence: 74%
See 1 more Smart Citation
“…In yet another study in Germany [56], on administration of garlic powder to 24 hypertensive patients for 3 months, their supine diastolic blood pressure fell by 11% and their standing systolic pressure fell by 12% as compared to non significant fall in a control of 23 patients. Similar results were obtained by Petkov in Russia also [57]. Onion and garlic organic sulfides can combine with NO and enhance vasodialation and reduce hypertension in mammals according to Ku et al [58] and Schwartz et al [37].…”
Section: Effect On Blood Pressuresupporting
confidence: 74%
“…The results show that garlic extract (250 lg/ml) acts as a growth suppressor for potentially immortal, cancerous and rapidly dividing cells owing to the increased sensitivity of such cells to garlic principles. Normal human skin fibroblasts grown in the presence of 100 and 250 lg/ml garlic extract could be specially passaged for [55][56][57][58][59][60][61][62][63][64][65][66] in about 475 days before they die. This is the first experiment in which an external agent prolonged the life span of cells to such an extent.…”
Section: Antiaging Effectsmentioning
confidence: 99%
“…18 Pektov (1979) has also cited several studies, which indicated that garlic and its extracts exhibit antihypertensive activity. 19 No substantial alterations were observed in pulse rate and systolic BP, when compared with control.…”
Section: Change In Cardiac Parametersmentioning
confidence: 83%
“…The extracts from hawthorn fruit are clinically effective in reducing blood pressure and total plasma cholesterol (14), and treating indigestion and retention of food due to improper diet or excessive intake of greasy food or meat. Some studies have established that hawthorn fruits are rich in proanthocyanidins and flavonoids (15)(16)(17). Such polyphenolic compounds can improve human health by reducing oxidative stress and providing activity associated with anti-cancer, anti-allergic, and anti-inflammatory effects (18,19).…”
Section: Introductionmentioning
confidence: 99%